Diurnal variation in DLCO and non-standardized study procedures may cause a false positive safety signal in clinical trials. (January 2022) - Kirla, Krishna Tulasi; Nemes, Szilárd; Betts, Joanne; Kristensson, Cecilia; Mo, John; Asimus, Sara; Sadiq, Muhammad Waqas; Redlich, Elke; Koernicke, Thomas; Fuhr, Rainard; Brailsford, Wayne; Keen, Christina; et al.
Abstract: Diffusing capacity for carbon monoxide (DLCO) was measured in a phase I single ascending dose study after inhalation of AZD8154 or placebo in healthy participants at baseline (DLCOBaseline ) and follow-up (DLCOFollow-up ) 6 days after dosing. Initially, DLCOFollow-up timepoint was 2 h earlier than the DLCOBaseline timepoint and clinically significant decreases in DLCOFollow-up (absolute change up to 19% from baseline and DLCO% predicted values less than 70) were observed then. The observed reduction in DLCOFollow-up was confirmed as a false positive finding after alignment of DLCO timings. As a consequence, when DLCO is used in clinical studies, measurements should be strictly standardized in relation to time of the day. Highlights: DLCO measurements might be affected by various factors in healthy volunteers. Measuring DLCO at different timings of a day led to significant decreased values. Factors affecting cardiac output should be standardized at each DLCO timepoint.